Rhabdomyolysis in Patients Hospitalized With COVID-19 Infection: Five Case Series - Shikha G. Khosla MD; Eric S. Nylen MD; Rahul Khosla MD (SAGE Publishing, 2020)
The novel SARS-CoV-2 virus (severe acute respiratory syndrome coronavirus 2) is now known to cause acute respiratory distress, cytokine storm, and coagulopathy. Multiple other manifestations have been published in recent literature. Rhabdomyolysis is a syndrome of muscle damage, with release of intracellular contents into circulation. It is characterized by marked elevations of creatinine kinase levels and myoglobinuria. In this article, we describe a series of 5 cases who were admitted with COVID-19 pneumonia and had severe muscle injury, as demonstrated by significant elevation (>5 times upper limit of normal) of creatinine kinase levels likely secondary to SARS-CoV-2 virus. The median age for these patients was 65 years, and most of them suffered from diabetes and hyperlipidemia. All patients were hypertensive males. Four out of 5 patients had preserved kidney function at baseline and were chronic kidney disease (CKD) stage 2 or better. However, most of them suffered significant kidney injury and at the time of discharge one patient was CKD stage 2 or better, 2 were CKD stage 3 or worse, and 2 patients had renal failure and died due to complications of SARS-CoV-2 infection.